2017
DOI: 10.1515/intag-2016-0085
|View full text |Cite
|
Sign up to set email alerts
|

Biomass valorisation of Arundo donax L., Miscanthus × giganteus and Sida hermaphrodita for biofuel production

Abstract: The potential of energy crops Sida hermaphrodita on organic farm'.A b s t r a c t. In the context of the growing demand for biomass, which is being encouraged by the EU directives on the promotion of the use of renewable energy, recent investigations have been increasingly focused on fast-growing energy crops. The aim of this study was to investigate the energy properties of three types of agricultural energy crops: Arundo donax L., Miscanthus × giganteus and Sida hermaphrodita. This investigation looked into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 22 publications
0
23
1
Order By: Relevance
“…The obtained results of lignocellulose composition in Sida hermaphrodita are slightly different from those presented by other authors [21,22]. Krička et al [22] reported that the contents of cellulose, hemicellulose, and lignin were about 40.1%, 27.2%, and 26.4%, respectively. These differences resulted from the present study investigating the composition of the substrate (Sida hermaphrodita mixed with cattle manure).…”
Section: Pretreatment Efficiencycontrasting
confidence: 77%
“…The obtained results of lignocellulose composition in Sida hermaphrodita are slightly different from those presented by other authors [21,22]. Krička et al [22] reported that the contents of cellulose, hemicellulose, and lignin were about 40.1%, 27.2%, and 26.4%, respectively. These differences resulted from the present study investigating the composition of the substrate (Sida hermaphrodita mixed with cattle manure).…”
Section: Pretreatment Efficiencycontrasting
confidence: 77%
“…Analysis of the Miscanthus lignocellulose components is mainly focused on four species: M. sacchariflorus, M. sinensis, M. floridulus, and M × g. According to the various reports in literature, the cellulose content of M × g (approximately 41%) is slightly higher than others while there is no significant difference in hemicellulose content among the four species (Tajana et al, 2017). The average cellulose content of M. sacchariflorus, M. sinensis, M. floridulus, and M × g are 38.9%, 37.6%, 37.2%, and 41.1%, respectively (Lee & Kuan, 2015).…”
Section: Components Of Miscanthus Biomassmentioning
confidence: 99%
“…In Europe in 2017, about 59% of renewable energy was provided from bioenergy, and globally about 10% of this is derived from agriculture [2]. Important bioenergy crops in Europe include maize (Zea mays L.) to produce biogas and bioethanol, and short rotation coppice [3] and Miscanthus [4] for the production of solid biofuel.…”
Section: Introductionmentioning
confidence: 99%